Design of artificial vascular devices: Hemodynamic evaluation of shear-induced thrombogenicity - Feaugas, Thomas; Newman, Gwenyth; Calzuola, Silvia Tea; Domingues, Alison; Arditi, William; Porrini, Constance; Roy, Emmanuel; Perrault, Cecile M. (Frontiers in Mechanical Engineering, 2023)
Blood-circulating devices such as oxygenators have offered life-saving opportunities for advanced cardiovascular and pulmonary failures. However, such systems are limited in the mimicking of the native vascular environment (architecture, mechanical forces, operating flow rates and scaffold compositions). Complications involving thrombosis considerably reduce their implementation time and require intensive anticoagulant treatment. Variations in the hemodynamic forces and fluid-mediated interactions between the different blood components determine the risk of thrombosis and are generally not taken sufficiently into consideration in the design of new blood-circulating devices. In this Review article, we examine the tools and investigations around hemodynamics employed in the development of artificial vascular devices, and especially with advanced microfluidics techniques. Firstly, the architecture of the human vascular system will be discussed, with regards to achieving physiological functions while maintaining antithrombotic conditions for the blood. The aim is to highlight that blood circulation in native vessels is a finely controlled balance between architecture, rheology and mechanical forces, altogether providing valuable biomimetics concepts. Later, we summarize the current numerical and experimental methodologies to assess the risk of thrombogenicity of flow patterns in blood circulating devices. We show that the leveraging of both local hemodynamic analysis and nature-inspired architectures can greatly contribute to the development of predictive models of device thrombogenicity. When integrated in the early phase of the design, such evaluation would pave the way for optimised blood circulating systems with effective thromboresistance performances, long-term implantation prospects and a reduced burden for patients.